Petroleum source rock characteristics of marine versus coastal settings: A comparative study between Madbi Formation of Masila Basin, Yemen and Nyalau formation of Sarawak, Malaysia - Abdullah, W.H. (Geological Society of Malaysia, 2017)
Two sets of contrasting oil-prone source rocks have been evaluated and compared - marine shales of the Jurassic Madbi Formation from Masila Basin, Yemen and Cenozoic coals and organic-rich sediments of the Nyalau Formation from Sarawak, Malaysia. An assessment based on organic facies characteristics, has been carried out on these sediments to distinguish, characterise and evaluate source rocks deposited in marine versus coastal plain depositional settings. Good source rock potential is suggested by the high TOC values of Madbi shales and organic-rich sediments of the Nyalau Formation. This is supported by high hydrocarbon indices of 450-752 mgHC/gTOC for the Madbi shales and 295-516 mgHC/gTOC for the Nyalau Formation coaly shales and coals. The Madbi shales have vitrinite reflectance values ranging from 0.74-0.88 Ro indicating an early mature to peak mature stage, while the Nyalau sediments have vitrinite reflectance values of 0.50-0.66, suggesting early maturity. The Madbi shale is expected to be a better source rock for oil as indicated from its higher abundance of Types I and II kerogen, compared to the Nyalau Formation which is dominated by Types II-III and III kerogen. On the other hand, good oil/gas generating potential is anticipated from the coals and carbargilite/coaly shales of the Nyalau Formation, based on their liptinite-rich nature and the predominance of n-alkene/alkane doublets and aromatic compounds. Samples from Madbi and Nyalau Formations were characterized by a variety of biomarker parameters based on GC and GC-MS techniques. Distribution of organic facies parameters such as Tm/Ts, Pr/Ph, pristane/n-C17, phytane/n-C18, oleanane/C30 hopane ratios and abundance of regular sterane (C27, C28 and C29) appear to reflect variations in depositional conditions and/or source input. Although there is a mixture of land-derived and marine-derived organic matter in both sediments, the depositional conditions of these formations can be distinguished based on these biomarker parameters, whereby the Madbi shales display organic facies characteristics of suboxic marine depositional conditions while the Nyalau sediments are consistent with paralic deposition within suboxic to oxic conditions, typical of terrestrial coastal plain environments. © 2017 Geological Society of Malaysia. All rights reserved.